Contemporary artists from the circumpolar region. Aslaug Juliussen and Ronald W. Senungetuk - Gullickson, Charis Ann (Universitetet i Tromsø, 2006)
This thesis is a comparative study investigating contemporary circumpolar art, with main focus on the Norwegian artist Aslaug Juliussen and the Alaskan artist Ronald W. Senungetuk. Both artists are Indigenous people, yet neither of them has a preference of being identified as Indigenous artists. In analyzing six artworks, three by each artist, the ambivalent nature of the “Indigenous label” will be examined. This study will show that it is difficult, in terms of an art historical perspective, to situate their art. Are categories such as Sámi or Alaska Native art misleading in terms of contemporary circumpolar art terminology? Does Juliussen’s and Senungetuk’s art reflect a common trend in contemporary circumpolar art? In a globalizing world, the term “Indigenous art” seems to be an all-inclusive term, which attempts to describe an entire group of very diverse artists. There seems to be a tendency to equate “Indigenous art” with handicraft. Both Juliussen’s and Senungetuk’s art defies this stereotype. Their art is remarkable because it breaks boundaries. In order to formulate a new approach to understanding contemporary circumpolar art, modern art theory will be employed, concentrating on the writings of the American theorists George Dickie and Arthur C. Danto. Their theories will accomplish two things. Firstly, determine where Juliussen’s and Senungetuk’s art can be positioned in regard to an art historical context. Secondly, explain how Juliussen’s use of non-modified objects can be understood as